NEGATIVE MOTH ER TONGUE LANGUAGE TRANSFER INTO ENGLISH WRITING LEARNING OF FIRST YEAR ADVANCED PROGRAM STUDENTS AT VIETNAM NATIONAL UNIVERSITY OF FORESTRY - Cong Ngoc, Pham (Journal of Forestry Science and Technology, 2016)
In learning a foreign language or English, learners face lots of challenges both of which are subjective and objective. One of those challenges is language transfer (or negative interferences) from mother tongue to English. This article presented the analysis and description of language transfer in English writing products of 80 first year students at Vietnam Forestry University. Language transfer is described in terms of lexis, syntax, and discourse which are selected from 3 types of writing: letter, description and narrative. The result pointed out some common errors in students’ writing because of their mother tongue interference. Of those writing errors, lexis level ones are the most common, and in different types of writing the error frequencies are also varied. Besides, the article supposed some main reasons why the student made such errors. As a result, a set of suggested solutions are given.